(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In this present situation, physical appearance is often balanced with self- perception, creating a challenging environment for Persons with Disabilities (PWDs) whose physique may not confirm to ableist standards. When real-life validation is seen low or negative, internal cognitive processes specifically self-talk become a critical determinant of mental well-being. This study explores how positive self- talk influences body dissatisfaction among persons with physical and sensory disabilities. Using a quantitative research design, data were collected from 50 participants (N =50) aged between 18 to 35 through purposive sampling method. Participants completed standardized self- report questionnaires measuring Positive Self-Talk (PSTS) and Body Dissatisfaction (BIS), with all responses kept confidential and collected under strict ethical guidelines. Preliminary findings suggests that individuals who engage in frequent positive self- talk experience significantly lower levels of body dissatisfaction (r = −0.72). Furthermore, comparative analysis indicates that the individuals with physical disabilities report higher dissatisfaction when compared to those with sensory disabilities. Framed within Cognitive Behavioral Theory, this study highlights how the human need for self- acceptance persists even when physical functionality is compromised, often finding expression through internal dialogue.